Drivers in determining medical tourism destination choice among international tourists using partial least squares method - Omar, Wan Marhaini Wan; Ismail, An Nur Nabila; Zainordin, Nik Mohamad Shamim Nik Mohd (Asian Journal of Empirical Research, 2023)
Medical tourism is a relatively new segment that has spurred the attention of major health care leaders across the globe over the decade. The global medical tourism market has shown extensive growth whereby global medical tourism generated USD11.56 billion in 2020 which increased to USD13. 98 billion in 2021. The amount is projected to grow to USD53.51 billion in 2028. In Asia region, few countries are playing their roles as medical destinations such as Thailand and Singapore. However, Malaysia continues to lag far behind the neighbouring countries in terms of number of international visitors. Thus, the study aims to determine the drivers of medical tourism destination choice among international tourists. Purposive sampling technique was applied for the study. A total of 115 responses from 21 different countries were collected through Medical Tourism Agency Website and their overseas branch. Data were analysed using partial least squares method. It can be concluded that lower cost and tourist attraction have paramount importance as drivers in choosing Malaysia as medical tourism destination. The outcome of the study will contribute to the field of medical tourism particularly in the context of improvising the marketing strategies and strategic partnership.